The lived experiences of providing nursing care in coastal areas: A qualitative study - Bayhakki; Nurul Huda; Yesi Hasneli (Journal of the Pakistan Medical Association, 2024)
Objective: To explore nurses’ experiences in providing care in coastal areas. Method: The phenomenological study was conducted from July to September 2020 in two coastal areas located in the Riau province of Indonesia, and comprised nurses working in public health centers, hospitals and district health offices. Data was collected using in-depth interviews. Data was subjected to thematic analysis. Results:Of the 13 nurses, 10(77%) were females and 3(23%) were males. The overall age range was 24-44 years. Four themes that emerged were health problems in coastal areas, obstacles in nursing care delivery, irrelevant duty, and procedures in delivering nursing care. There were a total of 10 sub-themes as well. Conclusion:Despite the challenged faced by the nurses, communities in coastal areas deserve to get due healthcare services. Keywords: Nursing care, Coastal areas, Experiences, Qualitative.